A Review of the Literature on Case Study Research - Patricia Anne Brown (Canadian Society for Studies in Education, 2008)
This paper presents a review of the literature on case study research and comments on the ongoing debate of the value of case study. A research paradigm and its theoretical framework is described. This review focuses extensively on the positions of Merriam (1998), Yin (1981, 1984, 1994, 1999, 2003a, 2003b, 2005), and Stake (1978/2000, 1994, 1995, 2005, 2008) as foundational writers in the area of case study research. As well, a range of voices in the debate related to case study research and its position as a research methodology in both the quantitative and qualitative paradigms are identified.